2019
DOI: 10.18034/gdeb.v8i2.101
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Blue Ocean Strategy on Organizational Performance

Abstract: The study deals with the blue ocean strategy (BOS) that offers users a framework for making uncontested market space and diverts the outlooks from the existing competition to the creation of innovative value and demand. The purpose of the study is to determine the influence of BOS on organizational performance. In this study, we systematically examine previous research on these topics of BOS. The findings show that there is a significant contribution of BOS to the enhancement of organizational performance. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Creating a market space with no competitors is an effort to create an uncompetitive market space and refers to the development of unique educational service offerings to differentiate from its competitors and create new market space that is difficult to imitate (Rahman & Choudhury, 2019). Natural elementary schools create an uncompetitive market space through 3 strategies, namely: 1) developing a unique educational philosophy; 2) developing special programs; and 3) utilization of technology.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Creating a market space with no competitors is an effort to create an uncompetitive market space and refers to the development of unique educational service offerings to differentiate from its competitors and create new market space that is difficult to imitate (Rahman & Choudhury, 2019). Natural elementary schools create an uncompetitive market space through 3 strategies, namely: 1) developing a unique educational philosophy; 2) developing special programs; and 3) utilization of technology.…”
Section: Resultsmentioning
confidence: 99%
“…Implementing the blue ocean strategy also has risks and challenges, such as requiring considerable costs and time to conduct market research and develop innovative educational programs (Rahman &;Choudhury, 2019). It is proven that natural elementary schools take ten years to develop nature-based education with a lot of financial capital such as land assets, facilities, curriculum development, training and human resource development, promotion, comparative studies to the development of new programs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, for effective use of CRM technology, an organization should establish a management system and a culture that emphasizes the customer. Rahman & Choudhury, (2019) have examined the role of technology integration, knowledge stores, and driving performance of CRM. Based on the random-effects model, they revealed that CRM technology assimilation and relational knowledge stores with higher levels lead to the superior performance of CRM.…”
Section: Literature Reviewmentioning
confidence: 99%